Road freight sustainability 4.0 : reducing CO2 emissions while improving profit - Kamdar, A.K (Transport Action Group, 2021)
Road freight operators are under increasing pressure from customers for lower transport rates, improved service, and lower Carbon emissions. Together with this, they have to ensure the safety of their drivers and fleet, as well as ensure that the company is profitable. These aims may seem contradictory and incompatible, but this book sets out a paint-by-numbers approach to lower Carbon emissions and increase profitability. Through an intimate understanding of the transport operations, and the implementation of a radical transformation, it is possible to reduce a road transport fleet Carbon emissions by more than 20%, and at the same time increase profits. Road Freight Sustainability 4.0 is a simplified approach to transport management, written in a conversational and engaging style to inspire a transformation that increases profit while serving society through lower Carbon emissions.The introduction of Battery Electric Trucks requires that in order for transport operators to embrace this pathway to Net Zero freight operations, they will have to be able to calculate their existing fleet Total Cost of Ownership cost per km, and be able to compare this to the Electric Truck Total Cost of Ownership cost per km. In addition, the transport operator will have to be able to demonstrate adequate profitability in order to be able to service the debt on the battery electric trucks which cost more than 3 times the price of the diesel equivalent (in 2022)